2007
DOI: 10.1007/s10661-007-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Cr, Cd, Cu, Zn and Fe in crab Charybdis longicollis and shrimp Penaeus semisulcatus from the Iskenderun Bay, Turkey

Abstract: Copper, chromium cadmium, iron and zinc concentrations were determined in marine crab Charybdis longicollis and marine shrimp Penaeus semisulcatus in order to assess the impact of industrial activities and the sinking of M/V Ulla ship. Liver, gill and muscle sample solutions prepared analyzed using the atomic absorption spectrophotometry technique. The order of the metal concentrations found in muscle of crab was: Cu>Cr>Fe>Zn>Cd, while in muscle of shrimp the order was different: Cr>Cu>Zn>Fe>Cd. The highest Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 27 publications
3
19
1
2
Order By: Relevance
“…Montes Nieto et al 47 detected metal accumulation in the gill of Carcinus maenas in Spain and they found a correlation between metal accumulation and degree of industrialization. Firat et al 48 found high concentrations of metals in shrimps (Penaeus semisulcatus) in Iskenderun Bay, Turkey, mainly caused by the wastewater drainage from the city nearby. This excessive metal concentration in river mounts of the upper gulf of Thailand may be caused by agricultural and industrial wastewater coming from upstream areas together with municipal wastewater from the cities nearby 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Montes Nieto et al 47 detected metal accumulation in the gill of Carcinus maenas in Spain and they found a correlation between metal accumulation and degree of industrialization. Firat et al 48 found high concentrations of metals in shrimps (Penaeus semisulcatus) in Iskenderun Bay, Turkey, mainly caused by the wastewater drainage from the city nearby. This excessive metal concentration in river mounts of the upper gulf of Thailand may be caused by agricultural and industrial wastewater coming from upstream areas together with municipal wastewater from the cities nearby 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Letters a, b, and c show differences among tissues. Data shown with different letters are statistically significant at p < 0.05 * p < 0.5; * * p < 0.1 (Student's t test); statistical differences between stations agricultural and industrial effluents and harbor operations were the main sources of marine pollution problems in this area (Yilmaz 2003;Cogun et al 2005;Türkmen et al 2005;Firat et al 2008). …”
Section: Stationmentioning
confidence: 91%
“…Numerous studies on heavy metal pollution from a wide spectrum on anthropogenic sources in various areas of Iskenderun Gulf have been carried out over the years (Kargin 1996;Yilmaz 2003;Cogun et al 2005;Türkmen et al 2005;Doygun and Alphan 2006;Firat et al 2008;Yüce and Alpar 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Its concentrations ranged from: 24.8-33.9 μg g -1 in muscle, 81.9-152.0 μg g -1 in viscera, 55.9-77.6 μg g The gills, present in the visceral samples, are structures with essential function in crustacean's respiration. They can potentially accumulate trace elements by absorption through the gills or by consumption of contaminated sediments (Firat et al, 2008). The metal concentrations in the gills reflect the metal concentrations in water (Yilmaz, 2003).…”
Section: Distribution Of Trace Elements In Tissuesmentioning
confidence: 99%